2017
DOI: 10.18632/oncotarget.20169
|View full text |Cite
|
Sign up to set email alerts
|

The significance of lumican expression in ovarian cancer drug-resistant cell lines

Abstract: PurposeThe aim of the present study is to determine the expression of LUM in drug-resistant ovarian cancer cell lines.MethodsDoxorubicin- (DOX), topotecan- (TOP) and vincristine- (VIN) resistant variants of the W1 ovarian cancer cell line were used in this study. We used quantitative real-time polymerase chain reactions to determine LUM mRNA levels. Protein expression was detected using Western blot and immunocytochemistry assays. Protein glycosylation was investigated using PGNase F digestion. Immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…In the cornea, lumican is expressed as the keratin sulfate proteoglycan, and is considered to possess the heterogeneous glycosaminoglycan [ 32 , 35 ]. Previously, various molecular weights of lumican between 37 and 250 kDa due to differences in glycosylation were detected from cell extracts by Western blot [ 36 , 37 , 38 , 39 , 40 ]. Our results also showed that various molecular weights of lumican between 37 and 250 kDa were observed in the cornea of rat, and increased lumican expression was observed in the cornea of the STZ rat (STZ) as compared to in that of the normal rat (Normal) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the cornea, lumican is expressed as the keratin sulfate proteoglycan, and is considered to possess the heterogeneous glycosaminoglycan [ 32 , 35 ]. Previously, various molecular weights of lumican between 37 and 250 kDa due to differences in glycosylation were detected from cell extracts by Western blot [ 36 , 37 , 38 , 39 , 40 ]. Our results also showed that various molecular weights of lumican between 37 and 250 kDa were observed in the cornea of rat, and increased lumican expression was observed in the cornea of the STZ rat (STZ) as compared to in that of the normal rat (Normal) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, an increasing body of evidence indicates that expression of ECM proteins in the tumor environment can play even more important role in drug resistance, especially from the clinical point of view [ 10 , 39 ]. It is worth mentioning that expression of ECM and related proteins is limited not only to tumor stroma and cancer-associated fibroblasts (CAF) but was also observed in tumor cells in vivo [ 10 , 12 , 15 , 40 , 41 ] and in cancer cell lines [ 13 , 37 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This form was overexpressed in cell lines resistant to PAC and TOP. Since we previously observed that COL3A1, LUM [ 14 , 15 ] and MYOT (under review) are secreted to cell culture media in drug resistant ovarian cancer cell lines, we were interested whether MGP can also be present in the culture medium. Indeed, we have noticed that MGP protein was present in culture media from investigated drug resistant cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations